Estudio de prefactibilidad para la instalación de una planta de producción de helado de fresa enriquecido con fitoesteroles y omega acidos - Campodónico Valcárcel, Fiorella (2015)
The present project seeks to demonstrate the viability of installing a producing plant of ice cream at a technological, economic and social level, because the manufacturing process is really simple and all the necessary machines can be found easily at good prices. This exposes the develop of the Project, determining basic points such as the demand and target market, the costs associated with the entire implementation process, including the productive process and third-party services among others. It also covers the evaluation of raw material and qualified workforce and technology. In this way, by the proper use of engineering tools, the convenience of the realization of this project will be demonstrated.